Recombinant human thrombomodulin inhibits neutrophil extracellular trap formation in vitro. Issue 1 (December 2016) - Shimomura, Yasuyo; Suga, Mika; Kuriyama, Naohide; Nakamura, Tomoyuki; Sakai, Toshikazu; Kato, Yu; Hara, Yoshitaka; Yamashita, Chizuru; Nagasaki, Hiroshi; Kaneki, Masao; Nishida, Osamu
Abstract The aim of this study was to investigate the effects of recombinant human-soluble thrombomodulin (rTM) on lipopolysaccharide (LPS)-induced, platelet-dependent neutrophil extracellular trap (NET) formation (NETosis). Human peripheral blood neutrophils and platelets were co-incubated with or without LPS (0.2 μg/ml) in the presence and absence of rTM (2 μg/ml). NETosis was confirmed by immunostaining and confocal microscopy. In the absence of platelets, LPS did not induce NETosis in the neutrophils. NETosis, however, was induced by LPS when neutrophils were co-cultured with platelets (64 % of neutrophils). Notably, rTM was able to fully inhibit NETosis in neutrophils cultured with platelets and in the presence of LPS. rTM did not induce NETosis in this co-culture system (p < 0.01 versus LPS in the absence of rTM). These results show that rTM can suppress LPS-induced platelet-dependent NETosis in vitro.